2019
DOI: 10.1099/jgv.0.001323
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus G9P[4], G9P[6] and G1P[6] strains isolated from children with acute gastroenteritis in Pune, western India, 2013–2015: evidence for recombination in genes encoding VP3, VP4 and NSP1

Abstract: Species A rotaviruses (RVAs) are genetically diverse pathogens. These are the most evolutionarily adaptable organisms, with a multitude of mechanisms for evolutionary change. To date, full-genome classification has been proved to be an excellent tool for studying the evolution of unusual rotavirus strains. As limited data are available from Pune (Maharashtra), western India, the current study was undertaken with the aim of understanding the genetic diversity in three (G1P[6], G9P[4] and G9P[4]) unusual RVA st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…In addition, cross protection could be due to other immune effector mechanisms other than antibody neutralization 41 . As previously documented in number of studies 42 44 , the current study noted the increase of G9P [4] genotype 5 years after implementation of ROTARIX vaccine. This observation requires further studies to establish if the ROTARIX vaccine has selected this genotype.…”
Section: Discussionsupporting
confidence: 82%
“…In addition, cross protection could be due to other immune effector mechanisms other than antibody neutralization 41 . As previously documented in number of studies 42 44 , the current study noted the increase of G9P [4] genotype 5 years after implementation of ROTARIX vaccine. This observation requires further studies to establish if the ROTARIX vaccine has selected this genotype.…”
Section: Discussionsupporting
confidence: 82%
“…The G9P[4]‐I2‐E1 strain also indicated double reassortant among DS‐1‐like G2P[4], Wa‐like G9P[8] and Wa‐like strains. Accordingly, several previous studies have indicated the presence of different genomic constellations of G9P[4] strains with double and triple‐reassortment events in Japan, 60,69,70 India, 71,72 United States, 73 the Czech Republic, 74 and Italy, 75 namely, G9‐P[4]‐I2‐R2‐C2‐M2‐A2‐N2‐T2‐E2‐H2, G9‐P[4]‐I2‐R2‐C2‐M2‐A2‐N2‐T1‐E2‐H2, G9‐P[4]‐I2‐R2‐C2‐M2‐A2‐N2‐T2‐E6‐H2, G9‐P[4]‐I2‐R2‐C2‐M2‐A2‐N1‐T2‐E6‐H2, and G9‐P[4]‐I2‐R2‐C2‐M2‐A2‐N1‐T2‐E2‐H2. These findings have provided substantial support to the hypothesis that uncommon DS‐1‐like strains originated primarily from reassortment events in the recent past involving contemporary G2P[4] strains as one parent and ordinary Wa‐like strains or animal RVA strains as the other.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, several previous studies have indicated the presence of different genomic constellations of G9P [4] strains with double and triple-reassortment events in Japan, 60,69,70 India, 71,72 United States, 73 the Czech Republic, 74 and Italy, 75 namely, G9-P…”
Section: Discussionmentioning
confidence: 99%
“…This postulates that reassortment of VP4 (from P[8] to P[4]) of G9 strains might have initially occurred even before 2010 and spread to the US, Benin, India, Czech, and Malaysia as these G9P[4] strains were placed in the same clade as shown in Figure 3. Sarawak G9P[4] strain in 2019 is highly likely to have been introduced from India since the strain clustered with the strains that had been associated with multiple outbreaks in India from 2010 to 2020, 28–30 a scenario similar to the observation that the G9P[4] strain was introduced in Argentina from another country 31 . The high evolutionary rate of G9 (1.87 × 10 −3 substitutions/site/year) 17 is the key factor in the phylodynamic and high variation in the VP7 epitope structure (Figure 6).…”
Section: Discussionmentioning
confidence: 92%